Clonal Hematopoiesis of Indeterminate Potential: New Insights from Recent Studies - Adrian Schmidt (healthbook TIMES. Oncology Hematology)
Clonal hematopoiesis of indeterminate potential (CHIP) is a condition characterized by accumulation of one or several somatic mutations in hematopoietic stem cells in the bone marrow. Recent studies have provided new data on the prevalence of CHIP mutations, which are relatively common in both cancer patients and the general population, and especially in older adults. Adverse clinical outcomes pertaining to hematopoietic clonality have also been observed in asymptomatic, apparently healthy individuals, such as cytopenia, cardiovascular complications, and/or overt blood cancers. However, there are currently no consensus guidelines on screening or monitoring for CHIP. New insights from recent studies will help to identify subgroups of patients who will benefit from routine CHIP screening, preventative measures, and early tailored intervention.